The impact of land policies on international migration: the case of the Brasiguaios - Estrada, M (International Migration Institute, 2015)
In the second half of the twentieth century, Brazilian and Paraguayan 'national’ land policies reshaped 'local’ social relations in both countries, especially in the eastern region of Paraguay. Between the 1960s and 1970s, the Brazilian land policies implemented to attract internal migrants for the development the central-eastern region followed a pattern of failures that motivated peasants and small farmers to leave the region. In the meantime, Paraguay was introducing a series of land policies to attract Brazilian migrants to develop the eastern side of Paraguay through the development of agriculture. Although Paraguay would achieve its objectives, land policies’ changes in the 1980s stimulated Brazilians to leave the country returning to Brazil. As a result of the migration processes led by land policies in both countries, Brazilian migrants returned to Brazil as self-defined Brasiguaios.